Eksploitasi Kerentanan dan Remote Access pada Windows 10 - Albert Christofen; Isram Rasal (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Exploitation is an activity carried out to gain benefits by harming others arbitrarily without responsibility. Exploitation is a threat in the field of Cyber Security that not only poses risks but also jeopardizes an individual's security and privacy. According to data from the Institute of Internal Auditors, financial losses due to cybercrime exploitation worldwide reached 8 trillion US dollars in 2023. In Cyber Security, one exploitation technique involves using Remote Access methods to take over access rights and enable remote system control. Based on this issue, the author conducts research on Remote Access using three different target models based on the Windows operating system. These three targets will demonstrate how vulnerabilities in an operating system can be exploited to gain Remote Access. The method for testing Remote Access involves identifying the vulnerabilities available in the target system. The study employs three techniques: exploiting the ms17-010 vulnerability, utilizing the SmbGhost vulnerability, and using a backdoor. The results show that all three approaches successfully penetrated the target system and made modifications.